2017
DOI: 10.3788/col201715.090002
|View full text |Cite
|
Sign up to set email alerts
|

Laser speckle imaging and wavelet analysis of cerebral blood flow associated with the opening of the blood–brain barrier by sound

Abstract: The cerebral blood flow (CBF) alterations related to sound-induced opening of the blood-brain barrier (BBB) in adult mice are studied using laser speckle contrast imaging (LSCI) and wavelet analysis of vascular physiology. The results clearly show that the opening of the BBB is accompanied by the changes of venous but not microvessel circulation in the brain. The elevation of the BBB permeability is associated with the decrease of venous CBF and the increase of its complexity. These data suggest that the cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…27 We suppose that after opening of the BBB the compensatory mechanisms of distribution of cerebral blood flow are involved; therefore, we cannot see the enlarged PVS. 26 The opening of the BBB is associated with the increase of diameter of the meningeal lymphatic vessels (the IHC and 2PLSM data). Indeed, the IHC data suggest that the diameter of these vessels is a 3.3-fold larger 1 h after opening of the BBB compared with one in the normal state (3.00 AE 0.01 μm versus 10.00 AE 0.07 μm, p < 0.05), according to the 2PLSM data 1.5-fold (12.00 AE 0.03 μm versus 17.00 AE 0.03 μm, p < 0.05).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…27 We suppose that after opening of the BBB the compensatory mechanisms of distribution of cerebral blood flow are involved; therefore, we cannot see the enlarged PVS. 26 The opening of the BBB is associated with the increase of diameter of the meningeal lymphatic vessels (the IHC and 2PLSM data). Indeed, the IHC data suggest that the diameter of these vessels is a 3.3-fold larger 1 h after opening of the BBB compared with one in the normal state (3.00 AE 0.01 μm versus 10.00 AE 0.07 μm, p < 0.05), according to the 2PLSM data 1.5-fold (12.00 AE 0.03 μm versus 17.00 AE 0.03 μm, p < 0.05).…”
Section: Discussionmentioning
confidence: 97%
“…To induce opening of the BBB, we used an audible sound (110 dB, 370 Hz): 60 s sound, then 60 s pause, and this cycle was repeated for 2 h. 26 This procedure was performed using a sound transducer in a Plexiglas ® chamber (with volume of 2000 cm 3 ) amplifying the effect of sound on the mice and not passing sound out.…”
Section: Confocal Imaging Of Lymphatic Drainage After the Opening Of Bbbmentioning
confidence: 99%
“…Further, the BBB permeability normalizes (about 4 h after the sound exposure), however, the prolonged accumulation of water in the brain parenchyma due to the long-lasting processes of recovery from vasogenic edema, probably, provokes increase in the intracranial pressure which induces once again BBB opening. 36 The latter process is rather weak as compared with changes in the venous CBF that occur in 90 min after the sound exposure. Let us consider how these changes can be quanti¯ed by the MSE-method.…”
Section: Resultsmentioning
confidence: 99%
“…Signi¯cant progress of in vivo analysis of cerebral dynamics provided the ability of in vivo study of BBB physiology, and the LSCI represents an appropriate tool that can be used for this purpose. In the previous paper, 36 we have shown that the BBB opens in 90 min after the sound exposure that leads to suppressed cerebral venous circulation. Further, the BBB permeability normalizes (about 4 h after the sound exposure), however, the prolonged accumulation of water in the brain parenchyma due to the long-lasting processes of recovery from vasogenic edema, probably, provokes increase in the intracranial pressure which induces once again BBB opening.…”
Section: Resultsmentioning
confidence: 99%
“…Механизмы, лежащие в основе установленного ФЗ на открытие ГЭБ, мало изучены, но есть доказательства, что вызванный ФЗ синглетный кислород ( 1 O 2 ) оказывает негативный эффект на регулирование сосудистого тонуса эндотелиальных клеток, сокращает приток и выход кальция из внутриклеточных запасов [11,12], тем самым запасы кальция истощаются в клетках и наступает ключевой момент в механизмах, лежащих в основе прямого влияния 1 O 2 во время сужения и расширения сосудов.…”
Section: научный отдел 426unclassified